Novel mutations of TYK2 leading to divergent clinical phenotypes. Issue 1 (7th October 2021) - Lv, Ge; Sun, Gan; Wu, Peilin; Du, Xiao; Zeng, Ting; Wen, Wen; Zhou, Lina; An, Yunfei; Tang, Xuemei; He, Tingyan; Zhao, Xiaodong; Du, Hongqiang
Abstract: Background: TYK2 deficiency is a rare primary immunodeficiency disease caused by loss‐of‐function mutations of TYK2 gene, which is initially proposed as a subset of hyper‐IgE syndrome (HIES). However, accumulating evidence suggests TYK2‐deficient patients do not necessarily present with HIES characteristics, indicating a vacuum of knowledge on the exact roles of TYK2 in human immune system. Method: Pathogenic effects of patients were confirmed by qRT‐PCR, Western blot, and protein stability assays. The responses to cytokines including IFN‐α/β/γ, IL‐6, IL‐10, IL‐12, and IL‐23 of peripheral blood mononuclear cells (PBMCs) from these patients were detected by Western blot, qRT‐PCR, and flow cytometry. The differentiation of T and B cells was detected by flow cytometry. Results: We described five more TYK2‐deficient cases presenting with or without hyper‐IgE levels, atopy, and distinct pathogen infection profile, which are caused by novel TYK2 mutations. These mutations were all found by high‐throughput sequencing and confirmed by Sanger sequencing. The patients showed heterogeneous responses to various cytokine treatments, including IFN‐α/β/γ, IL‐6, IL‐10, IL‐12, and IL‐23. The homeostasis of lymphocytes is also disrupted. Conclusion: Based on our findings, we propose that TYK2 works as a multi‐tasker in orchestrating various cytokine signaling pathways, differentially combined defects which account for the expressed clinical manifestations.